Acceptance of Cancer in Patients Diagnosed with Lung, Breast, Colorectal and Prostate Carcinoma - Urszula RELIGIONI; Aleksandra CZERW; Andrzej DEPTAŁA (Tehran University of Medical Sciences, 2015)
Background: The ability to accept illness is a major issue in the life of a person with cancer. Acceptance of disease is simultaneously conducted at two levels: the emotional and cognitive-behavioral one. It is consequential to cancer af-fecting numerous aspects of patient's life, i.e. the physical, mental, social and the spiritual area. The aim of the study was to verify the influence of socioeconomic factors on acceptance of illness in patients suffering from breast, lung, colorectal and prostate carcinoma. Methods: The study included 902 patients treated on an outpatient basis at the Center of Oncology, the Maria Skłodowska-Curie Institute in Warsaw, in the year 2013. The Paper and Pencil Interview (PAPI) technique was ap-plied. The questionnaire comprised basic demographic questions (socioeconomic factors) and Acceptance of Illness Scale (AIS) test estimating the level of disease acceptance in patients. Results: Prostate carcinoma patients scored highest (30, 39), whereas lung carcinoma patients scored lowest (23, 17) concerning illness acceptance according to the AIS scale. In all cases, linear dependence between the net income-per-household-member and the AIS score could be observed. Another diversification factor in the case of prostate carci-noma patients was the level of education. Yet one more dependence could be observed between the level of illness acceptance and chemotherapy over the course of past twelve months. Conclusion: The degree of disease acceptance is subject to a type of carcinoma. Patient income is an economic factor significantly affecting the acceptance of illness score.